A case of COVID-19-associated rhino-orbito-cerebral mucormycosis caused by Apophysomyces variabilis with a review of the literature - Erami, Mahzad; Mirhendi, Hossein; Momen-Heravi, Mansooreh; Hezaveh, Seyed Jamal Hashemi; Ahsaniarani, Amir Hossein; Sabet, Seddighe Sadat; Aboutalebian, Shima (Frontiers in Cellular and Infection Microbiology, 2022)
A fatal case of COVID-19-associated mucormycosis (CAM) affected a 40-year-old woman who was initially admitted to our hospital due to a SARS-CoV-2 infection. Her clinical condition worsened, and she finally died because of respiratory failure, hemodynamic instability, and mucormycosis with invasion into the orbit and probably the brain. According to DNA sequence analysis of the fungus isolated from the patient, Apophysomyces variabilis was involved. This is the first published case of CAM and the third case of mucormycosis due to this mold.